MOLECULAR BASED RAPID METHOD TO RESOLVE THE EXTENT OF DNA DAMAGES IN ACALYPHA INDICA - ARUMUGAM SENGOTTAIYAN; MUTHUSAMY GOVARTHANAN; THANGASWAMY SELVANKUMAR; KANDASAMY SELVAM (International Journal of Pharma and Bio Sciences, 2012)
The comet assay is a comparatively simple, but sensitive and well validated tool for measuring strand breaks in DNA in single cells. Cells were embedded in a thin layer of agarose on a microscope slide and lysed with detergent and high salt solution. Air pollution tolerance index of Acalypha indica growing in the natural conditions closest to road side and non road side were determined by comet assay.